2000
DOI: 10.1002/qj.49712656511
|View full text |Cite
|
Sign up to set email alerts
|

Observation and background adjoint sensitivity in the adaptive observation‐targeting problem

Abstract: Recent observation-targeting field experiments, such as the Fronts and Atlantic Storm-Track Experiment (FASTEX) and the NORth Pacific Experiment (NORPEX), have demonstrated that by using objective adjoint techniques it is possible, in advance, to identify regions of the atmosphere where forecast-error growth in numerical forecast models is maximally sensitive to the error in the initial conditions. 'Qpically, such techniques produce a field of the sensitivity of some aspect of the forecast to the analysis fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
129
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(134 citation statements)
references
References 12 publications
1
129
0
Order By: Relevance
“…Baker and Daley (2000) derived the equations of the sensitivity (gradient) of a scalar forecast aspect e(x a ) to observations and background for a linear analysis scheme (3)-(4):…”
Section: Sensitivity Analysis In Vdamentioning
confidence: 99%
See 1 more Smart Citation
“…Baker and Daley (2000) derived the equations of the sensitivity (gradient) of a scalar forecast aspect e(x a ) to observations and background for a linear analysis scheme (3)-(4):…”
Section: Sensitivity Analysis In Vdamentioning
confidence: 99%
“…The development of the adjoint of the forecast model and of the adjoint of the data assimilation system (adjoint-DAS) makes feasible the evaluation of the derivative-based, local sensitivity (Cacuci, 2003) of a scalar forecast aspect with respect to a large number of DAS input components. Adjoint-DAS estimation of the observation sensitivity was considered in the work of Baker and Daley (2000) and Doerenbecher and Bergot (2001) as a tool to design observation targeting strategies. Subsequently, Langland and Baker (2004) have shown that the combined information derived from the adjoint of the forecast model and the adjoint-DAS may be used to provide a detailed (all-at-once) assessment of the observation impact on reducing the forecast errors in variational data assimilation (VDA).…”
Section: Introductionmentioning
confidence: 99%
“…The adjoint approach to parameter sensitivity and impact estimation provides a basis to advance research in this area. Baker and Daley (2000) have shown that an all-at-once evaluation of the forecast sensitivity to observations may be performed by developing the adjoint of the data assimilation system (adjoint-DAS). The analysis of the information content of observations and the observation impact assessment through observation sensitivity and adjoint-DAS techniques are routine activities at NWP centres to monitor the observing system performance on reducing the short-range forecast errors (Langland and Baker, 2004;Trémolet, 2008;Baker and Langland, 2009;Cardinali, 2009;Daescu and Todling, 2009;Gelaro and Zhu, 2009;Gelaro et al, 2010;Cardinali and Prates, 2011;Lupu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Adjoint sensitivity represents the gradient of some forecast aspect with respect to the control variables of the model (i.e., initial conditions, boundary conditions, and parameters) [Errico, 1997] as well as to the observations [Baker and Daley, 2000]. Since adjoint sensitivity indicates the sensitivity of specific forecast aspects with respect to the model variables or observations at the initial time, it has been used in adaptive observations [e.g., Bergot, 1999].…”
Section: Introductionmentioning
confidence: 99%